Phenotypic resistance to lenacapavir and monotherapy efficacy in a proof-of-concept clinical study. (13th January 2022) - Margot, Nicolas; Vanderveen, Laurie; Naik, Vidula; Ram, Renee; Parvangada, PC; Martin, Ross; Rhee, Martin; Callebaut, Christian
Abstract: Background: Lenacapavir in vitro resistance selections identified seven mutations in HIV-1 capsid protein (CA) associated with reduced susceptibility. Objectives: To analyse lenacapavir activity against lenacapavir-associated resistance mutations in multiple assays. We also report Day 10 resistance analyses conducted in a Phase 1b study of lenacapavir (Study 4072) in people with HIV (PWH). Methods: Mutations were inserted in a proviral DNA clone by site-directed mutagenesis, and viruses ( n = 12) were generated by transfection. Sequences were used to generate single-cycle (SC) test vectors that were evaluated in a Gag-Pro assay, and replicative viruses were tested in a multicycle (MC) MT-2 assay to determine lenacapavir susceptibility. Study 4072 was a Phase 1b, double-blinded, placebo-controlled, dose-ranging, randomized study of lenacapavir in untreated PWH. Participants received a single dose of lenacapavir (up to 750 mg) or placebo (10 day monotherapy). CA resistance was characterized using genotypic and/or phenotypic assays. Results: Lenacapavir susceptibility in the SC assay showed an inverse relationship between replication capacity and resistance. In Study 4072, all 29 participants receiving lenacapavir showed a robust virological response with no rebound. At baseline, no participant had resistance mutations to lenacapavir, and all had WT susceptibility to lenacapavir. Post-monotherapy analyses revealed the emergence of CA mutation Q67H at Day 10 in two participants. Conclusions: In vitro assays confirmed that increased resistance to lenacapavir was associated with decreased replication capacity of mutant viruses. In the clinical study no pre-existing lenacapavir resistance was detected. Emergence of Q67H occurred at exposures below the dose used in current Phase 2/3 studies. These results support development of lenacapavir as an antiretroviral agent.